Life cycle assessment of Quayside Crane: A case study in China. (1st April 2017) - Wen, Bo; Jin, Qiang; Huang, Hong; Tandon, Puja; Zhu, Yuanhang
Abstract: China is an important Quayside Crane producer and exporter in the world. The Quayside Crane has been used as crucial equipment in container terminals and also in supporting towards the global trade momentum. However, it simultaneously impacts the environment negatively on air quality and in addition contributes adversely towards energy consumption. To reduce the deleterious environmental effects of the Quayside Crane so as to improve the sustainability of this industry, evaluation of its environmental impacts through life cycles is acute necessary. This research undertook a cradle-to-grave life cycle assessment for a Quayside Crane made in China. Its purpose was to identify the key processes that effected the environment, as well as, sought out opportunities for improving the environmental profiles of Quayside Cranes. The inventory data was obtained from on-site investigations of Quayside Crane producers in Shanghai, China. The environmental impacts were evaluated using the ReCiPe method at midpoint level and operating the GaBi 6.0 assessment software. The results showed that nearly all environmental impact categories and life cycle costs were relatively high in the utilization stage. Steel production stage was the most important driver to the categories that impact environmental degradation, such as freshwater ecotoxicity, metal depletion, freshwater eutrophication and ozone depletion. Accordingly recovery of materials, such as steel reuse after refurbishment in the end-of-life stage could notably diminish most of the environmental impacts. In addition, sensitivity analysis and economic analysis were employed to promote the reliability of the life cycle assessment results. Based on these findings, several improvements could be put forward, for instance, optimized design for motor efficiency of the Quayside Crane was recognized as the most effective way to reduce the environmental impacts which should be urgently amended. The life cycle assessment could help decision-makers to know the key points that should be streamlined to make the Quayside Crane more reliable, energy-efficient, technologically and environmentally sustainable. Highlights: Quayside Crane sector in China is assessed by LCA. Field data are collected from the leading company. Life cycle cost is analyzed and coupled to environmental impacts simultaneously. Lifting motor is identified as the key point to improve performances.